Factors Affecting the Availability and Utilization of Essential Medicines in India: A Systematic Review - Trivedi Poonam; Raval Devang; Saha Somen; Prajapati Hitesh; Gautam Rupal; Jagadeesh K V; Rajshekhar Kavitha (Wolters Kluwer Medknow Publications, 2024)
Essential medicines or drugs are recognized as highly cost-effective components within contemporary healthcare, demonstrating significant potential for improving health outcomes. The provision of essential medicines directly impacts the functioning of healthcare facilities, resulting in financial hardship. This review aims to fill knowledge gaps by examining obstacles hindering access and utilization of essential medicines in India. This study conducted a comprehensive evidence synthesis, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, to analyse articles on the availability and utilization of essential medicines in India. The search strategy included various databases and keywords. Published, peer-reviewed articles focusing on the National/ State List of Essential Medicines and meeting specific criteria were considered. Data items included essential medicines, drug availability, utilization, and challenges. Data was extracted, synthesized, and analysed using thematic framework analysis. Out of 1,129 articles, 11 were selected for review. Studies consistently highlighted the inadequate availability of essential medicines in different Indian states. Availability of essential medicines varies in the range of 17-51 percent across major states of India. Stock-outs of medicines vary from 4 to 14 weeks. Governance issues including differential procurement mechanisms across states of India, hinder seamless availability of essential medicines. Other challenges included distribution and purchasing system inefficiencies, governance-related issues, and facility/ user-level challenges impacting drug utilization. Disruptions in utilization were observed due to improper prescription practices and non-availability of affordable options. Accessibility and affordability also affected drug utilization. Issues with supply chain management and conflicting guidelines further contributed to the obstacles faced in ensuring availability and utilization of essential medicines in India. Ensuring the availability, accessibility, and affordability of essential medicines is of utmost importance. The public health system needs to strengthen its procurement and distribution management. Strengthening the logistics support for an efficient supply of essential medicines will reduce the time lag in receipt of drugs. Guidelines on essential drugs prepared by the National Health System Resource Centre need to be strictly adhered to and monitored in inventory management system. There is an urgent need to develop a sustainable model for achieving uniformity in the availability and utilization of essential medicines in India.